Transparency and Accountability Based on The Concept of â€œPada Gelahangâ€ Enhancing Village Financial Management - Budiasni, Ni Wayan Novi; Ayuni, Ni Made Sri (International Journal of Social Science and Business, 2020)
Along with the increase in the amount of village funds and the efforts to decrease the mismanagement carried out by the government, the Government strives to defend the WTP opinion by adapting local wisdom in managing finances. This study aims to analyze the variables of transparency and accountability based on the concept of pada gelahang in the village financial management. The research was a quantitative with SEM (Structural Equation Modelling) analysis tool and using PLS (Partial Least Square) method. The sample of this study is 57 Village in Buleleng Regency. The results showed that transparency had an effect on the management of village finances (tcount >ttable = 3,501>1,960) and accountability had an effect on the management of village finances (tcount >ttable = 5,571>1,960). Thus, it is found that transparency and accountability based on the concept of pada gelahang have an effect on village financial management. The concept of the pada gelahang has the meaning of equality, togetherness and mutual assistance reflected in the financial management of the village that is transaparan and accountable.